1998
DOI: 10.1001/archpsyc.55.12.1084
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gray Matter, White Matter, and Cerebrospinal Fluid Distributions in Schizophrenic Patients, Their Siblings, and Controls

Abstract: Background: Cortical gray matter volume reductions and cerebrospinal fluid (CSF) volume increases are robust correlates of schizophrenia, but their sources have not been established conclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
128
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 238 publications
(150 citation statements)
references
References 34 publications
19
128
2
1
Order By: Relevance
“…Since the time of Kraepelin, the nonpsychotic relatives of schizophrenics have often been noted to manifest quantitative abnormalities in personality. 31,32 These findings were later extended to other 'endophenotypes', such as cognition, 33,34 psychophysiology, 35,36 and brain structure 37,38 that are thought to be related to the expression of genes relevant to the etiology of schizophrenia (reviewed by Siever and Davis 39 ).…”
Section: The Effects Of Genes In Nonpsychotic Relativesmentioning
confidence: 99%
“…Since the time of Kraepelin, the nonpsychotic relatives of schizophrenics have often been noted to manifest quantitative abnormalities in personality. 31,32 These findings were later extended to other 'endophenotypes', such as cognition, 33,34 psychophysiology, 35,36 and brain structure 37,38 that are thought to be related to the expression of genes relevant to the etiology of schizophrenia (reviewed by Siever and Davis 39 ).…”
Section: The Effects Of Genes In Nonpsychotic Relativesmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies in unaffected family members (FM) of schizophrenia patients suggest that genetic factors affect brain structure (1)(2)(3)(4)(5), with FM generally showing characteristics of brain structure in-between patients and healthy controls (HC). Likewise, high risk individuals such as patient offsprings with no clinical history of psychosis, have similar structural abnormalities, most notably in hippocampus and amygdala, with some contradictory results (6-9) having being reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Several such studies have found that frontal and temporal lobe regions may be particularly affected (4,5,16,17). Whether this regional pattern reflects differential involvement of specific cytoarchitectonic areas remains to be determined but potentially could be resolved by voxel-based morphometric analysis (18,19).…”
mentioning
confidence: 99%